Informe de pasantía realizada en la compañía Mainco Health Care S.A.S en el área de comercio exterior. (2020)
The purpose of this report is to present the final result of the internship carried out in the foreign trade area of the company MAINCO HEALTH CARE S.A.S. during the months of February, March and April of the year 2020, to achieve an analysis prior to the guaranteed fulfillment in the productive stage of the internships. The research is carried out mainly to analyze the position of foreign trade analyst and his functions in the importation process, such as the development of purchase orders abroad, generation of currency reports to the Republic Bank and the DIAN. Compliance with the expected time of the imported merchandise, measurement in the inventory stock. Analysis of the costs generated in each import, as well as the weekly meetings with the production area where the references to be purchased are detailed.Mainco Health Care S.A.S was founded on November 27, 1997 by its current owner, Ms. Janneth Moreno Castañeda, it is there that Mainco changed its name to the manufacture, marketing and import of high quality disposable clothing. It currently has two lines of sterile and non-sterile products. At present it is one of the most recognized companies nationally and internationally and recognized in the country of Panama, it is planned that in 2021 Mainco will be incorporated into the Pacific free zone and thus implement its exports to more countries with greater security. and easier way for customs normality.